Pengaruh Intensitas Persediaan, Intensitas Aset Tetap dan Beban Iklan terhadap Agresivitas Pajak - Rezka Sari Ananda; Mulyani Mulyani (JURNAL PUNDI, 2023)
This study aims to determine the effect of inventory intensity, fixed asset intensity and advertising expenses on tax aggressiveness in Property and Real Estate companies listed on the Indonesian stock exchange in 2017-2021 which consists of 73 companies. This research method uses a quantitative method with a purposive sampling technique which produces a sample of 14 companies with 5 (five) years of observation. The data analysis method uses descriptive statistical analysis and hypothesis testing with a significance level of 5%. The test tool used is E-views 9. The results of this study indicate that inventory intensity variable has no effect on tax aggressiveness, while the variable intensity of fixed assets and advertising expenses has an effect on tax aggressiveness. Simultaneously the variable inventory intensity fixed asset intensity and advertising expenses affect tax aggressiveness. Keywords: Inventory Intensity, Fixed Aset Intensity, Advertising Expense, Tax Aggressiveness.